1989
DOI: 10.1159/000116412
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Chloroquine Myopathy: Morphological and Biochemical Studies

Abstract: Morphological and biochemical studies were performed on the soleus muscles of rats receiving a daily intraperitoneal injection of 50 mg chloroquine chloride (CQ) per kilogram of body weight. Light microscopy showed mild to moderate variations in fiber size, numerous dense membranous bodies and vacuoles. The vacuoles were ringed by material that was intensely basophilic in hematoxylin-eosin preparations, resembling rimmed vacuoles in the muscle fibers of distal myopathy. Segmental degradation or necrosis was of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

1993
1993
2009
2009

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Previous studies have reported marked and early accumulation of rimmed vacuoles consisting of dense granular bodies and variously sized vacuoles in the denervated muscles of chloroquine-treated rats [1][2][3] . By contrast, these vacuoles were very rare in the contralateral, innervated chloroquine-treated muscles as well as in the innervated and denervated muscles of saline-treated rats.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous studies have reported marked and early accumulation of rimmed vacuoles consisting of dense granular bodies and variously sized vacuoles in the denervated muscles of chloroquine-treated rats [1][2][3] . By contrast, these vacuoles were very rare in the contralateral, innervated chloroquine-treated muscles as well as in the innervated and denervated muscles of saline-treated rats.…”
Section: Discussionmentioning
confidence: 85%
“…Chloroquine, a lysosomotrophic agent, modulates autophagic protein degradation in the lysosome system, thereby inducing the formation of rimmed vacuoles consisting of dense granular bodies and vacuoles including many variably sized and shaped autophagosomes in skeletal muscles [1][2][3] . We previously demonstrated an increased number of rimmed vacuoles in denervated chloroquine-treated rat muscle but not in innervated chloroquine-treated muscle or in innervated or denervated muscles of saline-treated rats [2] .…”
Section: Introductionmentioning
confidence: 99%
“…TOXICOLOGIC PATHOLOGY nor the pharmacology of the compounds adequately account for the myotoxic effects of the drugs (Schmalbruch, 1980;Kumamoto et al, 1989). Cationic amphiphilic drugs may accumulate in lysosomes, inhibit activity of lysosomal enzymes, and bind to phospholipids in membranes in general (Hostetler, 1984;Reasor, 1989).…”
Section: Resultsmentioning
confidence: 99%
“…All of these effects could theoretically occur independently of the formation of LLBs. It has also been suggested that the accumulation of material within lysosomes injures lysosomal membranes and increases their permeability or makes the lysosomes fragile (Kumamoto et al, 1989). Subsequent leakage of proteolytic enzymes into the cytoplasm could damage myofibrils.…”
Section: Resultsmentioning
confidence: 99%
“…Phospholipidosis is sometimes associated with tissue injury in preclinical animal species and man; however, establishing a direct relationship between phospholipid accumulation and cell injury is difficult (Fardeau et al, 1979;Schmalbruch, 1980;Kumamato et al, 1989;Reasor, 1989;Halliwell, 1997;Yano, 2002). For this reason, it is important that safety biomarkers are identified in preclinical studies for the clinical monitoring of patients.…”
Section: Discussionmentioning
confidence: 99%